IMPLEMENTASI PEMBANGUNAN INFRASTRUKTUR DALAM PERCEPATAN PEMBANGUNAN DAERAH PEDALAMAN DI KECAMATAN MALINAU SELATAN KABUPATEN MALINAU - Royanto Royanto; Adam Idris; Nur Fitriyah (Magister Administrasi Publik FISIP Universitas Mulawarman, 2019)
The purpose of this research is to know how the Implementation of Infrastructure Development in Acceleration of Development of Inland Region in Kecamatan Malinau Selatan Malinau District. This research uses descriptive research and will be analyzed by using the inductive approach method. From the results of the research, Implementation of Infrastructure Development in Acceleration of Rural Development in Kecamatan Malinau Selatan has been running well, from year to year, there is a significant change but still needed sustainable development. Keywords: Infrastructure, Development, Acceleration